Cobalt(III)-Catalyzed Redox-Neutral Coupling of Acrylamides with Activated Alkenes via C–H Bond Activation - Keerthana, Meledath Sudhakaran; Manoharan, Ramasamy; Jeganmohan, Masilamani (Synthesis, 2020)
A cobalt(III)-catalyzed coupling of substituted acrylamides with maleimides in the presence of 30 mol% pivalic acid providing olefin-migrated succinimide derivatives in a redox-neutral manner is described. The coupling reaction was examined with various substituted acrylamides and maleimides. The scope of the C–H alkylation reaction was also examined with substituted acrylates. A possible reaction mechanism involving a five-membered cobaltocycle as a key intermediate is proposed.
Keywords: acrylamides; maleimides; C–H activation; alkylation; succinimides; acrylates; cobalt